Effects of aliskiren on stroke in rats expressing human renin and angiotensinogen genes. - Kristin Schmerbach; Thiemo Pfab; Yi Zhao; Juraj Culman; Susanne Mueller; Arno Villringer; Dominik N Muller; Berthold Hocher; Thomas Unger; Christa Thoene-Reineke (PLoS ONE, 2010)
Objective Pre-treatment with angiotensin receptor blockers is known to improve neurological outcome after stroke. This study investigated for the first time, whether the renin inhibitor aliskiren has similar neuroprotective effects. Methods Since aliskiren specifically blocks human renin, double transgenic rats expressing human renin and angiotensinogen genes were used. To achieve a systolic blood pressure of 150 or 130 mmHg animals were treated with aliskiren (7.5 or 12.5 mg/kg*d) or candesartan (1.5 or 10 mg/kg*d) via osmotic minipump starting five days before middle cerebral artery occlusion with reperfusion. Infarct size was determined by magnetic resonance imaging. mRNA of inflammatory marker genes was studied in different brain regions. Results The mortality of 33.3% (7 of 21 animals) in the vehicle group was reduced to below 10% by treatment with candesartan or aliskiren (p<0.05). Aliskiren-treated animals had a better neurological outcome 7 days post-ischemia, compared to candesartan (Garcia scale: 9.9±0.7 vs. 7.3±0.7; p<0.05). The reduction of infarct size in the aliskiren group did not reach statistical significance compared to candesartan and vehicle (24 h post-ischemia: 314±81 vs. 377±70 and 403±70 mm(3) respectively). Only aliskiren was able to significantly reduce stroke-induced gene expression of CXC chemokine ligand 1, interleukin-6 and tumor necrosis factor-alpha in the ischemic core. Conclusions Head-to-head comparison suggests that treatment with aliskiren before and during cerebral ischemia is at least as effective as candesartan in double transgenic rats. The improved neurological outcome in the aliskiren group was blood pressure independent. Whether this effect is due to primary anti-inflammatory mechanisms has to be investigated further.